Manajemen Komunikasi: Faktor Penghambat Dan Pendorong Berkembangnya Manajemen Komunikasi Sebagai Tindakan Lembaga Keuangan Daerah - Ni Nyoman Wulan Antari (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
In the world economy, communication is one of the things that might affect the quality of a service it to customers.Good communication can motivate each worker to continue performing in serving kebpelanggan present and to provide convenience customers to interact and transact in a company without ever think to turn to other firms.This digital diera really makes a difference to a company because management and staff can communicate more easily.Communicating information regarding the development of a company to pelangganpun is very easy to do, moreover financial information related to.This study will try describes the phenomena of management communication as the transformation of financial management service diera globalization.The research was in the customary village tanjung bungkak denpasar with 20 the informants. Data collecting techniques performed by using interviews and documentation.The result of this research is that there are several supporting factors supporting communication management as an act of the local financial institutions among others support management and ideas and the availability of funding.